Development of a multiplex system to assess DNA persistence in taphonomic studies. Issue 24 (December 2013) - Nazir, Muhammad S.; Iyavoo, Sasitaran; Alimat, Sharizah; Zahra, Nathalie; Sanqoor, Sheikha H.; Smith, Judith A.; Moffatt, Colin; Goodwin, Will
<x xml:space="preserve">Abstract</x> In this study, we have developed a PCR multiplex that can be used to assess DNA degradation and at the same time monitor for inhibition: primers have been designed to amplify human, pig, and rabbit DNA, allowing pig and rabbit to be used as experimental models for taphonomic research, but also enabling studies on human DNA persistence in forensic evidence. Internal amplified controls have been added to monitor for inhibition, allowing the effects of degradation and inhibition to be differentiated. Sequence data for single‐copy nuclear recombination activation gene (RAG‐1) from human, pig, and rabbit were aligned to identify conserved regions and primers were designed that targeted amplicons of 70, 194, 305, and 384 bp. Robust amplification in all three species was possible using as little as 0.3 ng of template DNA. These have been combined with primers that will amplify a bacterial DNA template within the PCR. The multiplex has been evaluated in a series of experiments to gain more knowledge of DNA persistence in soft tissues, which can be important when assessing what material to collect following events such as mass disasters or conflict, when muscle or bone material can be used to aid with the identification of human remains. The experiments used pigs as a model species. When whole pig bodies were exposed to the environment in Northwest England, DNA in muscle tissue persisted for over 24 days in the summer and over 77 days in the winter, with full profiles generated from these samples. In addition to time, accumulated degree days (ADD) were also used as a measure that combines both time and temperature—24 days was in summer equivalent to 295 ADD whereas 77 days in winter was equivalent to 494 ADD.